Long-term outcome of using Ara-C or not in children’s APL - Yingjin Zhang; Changwen Xue; Chao Wu; Wenyu Yang; Yao Zou; Ye Guo; Yumei Chen; Xiaojuan Chen; Xiaofan Zhu; Li Zhang (Blood Science)
The use of cytarabine (Ara-C) in treating acute promyelocytic leukemia (APL) is controversial. This study was conducted to demonstrate the effect of treatment with or without Ara-C on long-term event-free survival (EFS) or overall survival (OS). All patients received all-trans retinoic acid (ATRA) + arsenic trioxide (ATO) induction therapy, followed by the course of idarubicin (IDA) and ATO, then were randomly allocated to 2 groups for consolidation therapy, with patients in the daunorubicin (DNR) group received DNR, in the DNR + Ara-C (DA) group received DNR + Ara-C. Maintenance therapy consisted of oral ATRA, 6-mercaptopurine, and methotrexate for 1.5 years. Thirty patients in DA group and 35 patients in DNR group, all achieved complete remission. At follow-up, there was 1 death and 3 relapses in DNR group, compared to none in DA group. There was no statistically significant difference in EFS (P = 0.140) and OS (P = 0.398) between 2 groups, with EFS being 100% in DA group and 91.4% ± 0.047 in DNR group, and OS being 100% in DA group and 97.1% ± 0.028 in DNR group. Our study found no prognostic significance of Ara-C, this may be related to the small sample size. We still recommend the addition of Ara-C during treatment, which has a more positive impact on early remission and late prognosis of patients.